Классификация и способы перевода культурно-специфической лексики - Василенко, Н.А.; Мележик, К.А. (Культура народов Причерноморья, 2013)
Статья посвящена актуальной на сегодняшний день проблеме исследования культурно-
специфических реалий и углубления знаний о концептуальном поле межкультурной коммуникации,
которая активно развивается в условиях расширения межкультурных контактов. В статье ставится
задача рассмотреть содержание терминов межкультурная коммуникация и культурно-специфические
реалии, опираясь на понятия интерлингвокультурного субстрата и функционального дуализма. На
основе проведенного исследования автором предлагается выделить основные способы передачи
культурно-специфической лексики.
Ключевые слова: перевод, культурно-специфическая лексика, культуронимы, транскрибирование,
инолингвокультурный субстрат. Стаття присвячена актуальній на сьогоднішній день проблемі дослідження культурно-
специфічних реалій і поглиблення знань про концептуальне поле міжкультурної комунікації, яка активно
розвивається в умовах розширення міжкультурних контактів. У статті ставиться завдання
розглянути вміст термінів міжкультурна комунікація і культурно-специфічні реалії, спираючись на
поняття інтерлінгвокультурного субстрата і функціонального дуалізму. На основі проведеного
дослідження автором пропонується виділити основні способи передачі культурно-специфічної лексики.
Ключові слова: переклад, культурно-специфічна лексика, культуроніми, транскрибування,
інолінгвокультурний субстрат. The article is devoted to a problem of research of cultural and specific realias which are actual today
and increasing knowledge of a conceptual field of cross-cultural communication which actively develops in the
expansion conditions of cross-cultural contacts. The task in the article is to consider the contents of terms crosscultural
communication and cultural-specific realias, relying on the concepts of an interlingvoсultural
substratum and functional dualism. On the basis of the conducted research it is offered to allocate by the author
the main ways of translation of cultural and specific vocabulary on the material of sampling from publicistic and
bélles-léttres texts. Connection of culture and communication is considered in the article. The analysis
researchers' views is provided that various functions of culture are connected with language functions.
Characteristics of the cross-cultural language contacts are allocated and described in the article. They are
carrying out in the conditions of bilingualism where very important role is played by cultural and specific realias
of languages. Methods of tranlation of realias in summary are reduced generally to two: transcription
(transliteration) and translation. On the basis of studying methods of translation cultural and specific
vocabulary is established that prevailing way of translation of realias is transcription by means of which 60% of
the selected examples are translated, and further follow: approximate translation, transliteration and tracing.
Keywords: translation, cultural and specific vocabulary, kulturonim, transcription, interlingvoсultural
substratum.